The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1183/13993003.00011-2020
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and determinants of exhaled nitric oxide trajectories in schoolchildren over a 7-year period

Abstract: Fractional exhaled nitric oxide (FENO50), a marker of allergic airway inflammation, is used in respiratory research and asthma clinical care; however, its trajectory with increasing age during childhood has not been well characterised. We examined FENO50 longitudinally during a period of important somatic growth to describe trajectories across childhood and adolescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Indeed, our data suggest that differences in height (>80cm range in both MAAS and SEATON cohorts) markedly influence FeNO, particularly in relation to the higher percentile lines. Consistent with this, Garcia et al used repeated measures within children going through puberty and reported a substantial increase in FeNO between 8-16 years, with tracking of personalised FeNO measurements, and highlighted the limitations of fixed FeNO reference values [13]. Whilst using a fixed single FeNO cutoff may seem easier for clinicians to implement, technology allowing input of demographic data and automatic calculation of % predicted values (as for spirometry), would streamline the utility of a height-adjusted approach in practice.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Indeed, our data suggest that differences in height (>80cm range in both MAAS and SEATON cohorts) markedly influence FeNO, particularly in relation to the higher percentile lines. Consistent with this, Garcia et al used repeated measures within children going through puberty and reported a substantial increase in FeNO between 8-16 years, with tracking of personalised FeNO measurements, and highlighted the limitations of fixed FeNO reference values [13]. Whilst using a fixed single FeNO cutoff may seem easier for clinicians to implement, technology allowing input of demographic data and automatic calculation of % predicted values (as for spirometry), would streamline the utility of a height-adjusted approach in practice.…”
Section: Discussionmentioning
confidence: 80%
“…Of 214 symptomatic and treatment-naïve patients referred to the RADicA study from primary care for possible asthma, 73 (median [IQR] age: 11 [8][9][10][11][12][13][14] years, 47.9% male, 54.8% white) were aged 22 years or younger (age-matching for chart development cohort), had a definitive diagnostic outcome (51 had asthma, 22 did not have asthma), and a measurement of FeNO before treatment was initiated (Table E18). Data from these participants were used to assess sensitivity and s pecificity of FeNO percentile charts for asthma diagnosis.…”
Section: Using Feno Percentile Chart For Asthma Diagnosis In Symptoma...mentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous longitudinal analysis, FeNO 50 was found to have a strong positive linear association with height across this age range in children without asthma [30]. To complement the previous analysis relating longitudinally assessed FeNO 50 to height, here we relate longitudinally assessed NO parameters (from the up to 2 repeated assessments of multiple flow FeNO) to standardized height (population-mean centered: 162.7 centimeters and population-SD scaled: 8.75 centimeters).…”
Section: Methodsmentioning
confidence: 94%
“…Our findings add to the limited literature on associations of NO parameters with height/age. A previous analysis using longitudinal FeNO 50 data from the same cohort over a longer follow-up period, from ages 8-16, found that FeNO 50 increased approximately linearly with height and FeNO 50 increased nonlinearly with age [30].…”
Section: Discussionmentioning
confidence: 99%